The relationship between social support with career maturity among high school students in Kisaran : Hubungan antara dukungan sosial dengan kematangan karir pada siswa-siswi SMA di Kisaran - Dedek Prilyanti; Sri Supriyantini (Talenta Publisher, 2021)
The research method used is quantitative. The samples used were students of 11th grade (N = 190). Measuring tool used in this study is the scale of social support was based on the theory by House (in Smet, 1994) and Career Maturity Inventory (CMI) from Crites who have adapted to the culture of Indonesia by Taganing, Muluk, dan Rifameutia (2007). The data research was processed using Pearson Product Moment. Results of the data analysis showed a positive relationship between the social support of the career maturity with p < .001 Metode penelitian yang digunakan adalah kuantitatif. Subjek penelitian yang digunakan adalah siswa-siswi kelas XI (N = 190). Alat ukur yang digunakan dalam penelitian ini adalah skala dukungan sosial disusun berdasarkan teori House (dalam Smet, 1994) dan Inventori Kematangan Karir (Career Maturity Inventori) dari Crites yang telah diadaptasi sesuai budaya Indonesia oleh Taganing, Muluk, dan Rifameutia (2007). Data penelitian ini diuji menggunakan Pearson Product Moment. Hasil analisa data menunjukkan adanya hubungan yang positif antara dukungan sosial dengan kematangan karir sebesar sig p < .001.